Neutron lifetime measurement with pulsed cold neutrons. (4th December 2020) - Hirota, K; Ichikawa, G; Ieki, S; Ino, T; Iwashita, Y; Kitaguchi, M; Kitahara, R; Koga, J; Mishima, K; Mogi, T; Morikawa, K; Morishita, A; et al.
Abstract: The neutron lifetime has been measured by comparing the decay rate with the reaction rate of $^3$ He nuclei of a pulsed neutron beam from the spallation neutron source at the Japan Proton Accelerator Research Complex (J-PARC). The decay rate and the reaction rate were determined by simultaneously detecting electrons from the neutron decay and protons from the $^3$ He(n, p)$^3$ H reaction using a gas chamber, the working gas of which contains diluted $^3$ He. The measured neutron lifetime was $898\, ±\, 10\, _{\rm stat}\, ^{+15}_{-18}\, _{\rm sys}\, $ s.